Zinc Supplementation for Acrodermatitis Enteropathica Overlapped with Psoriasiform Lesions - Wang L; Zou S; Zhu Y (Dove Medical Press, 2024)
Liangzhe Wang,* Shuaijun Zou,* Yuanjie Zhu Department of Dermatology, Naval Medical Centre, Naval Medical University, Shanghai, 200052, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuanjie Zhu, Department of Dermatology, Naval Medical Centre, Naval Medical University, 388 West Huaihai Road, Shanghai, People's Republic of China, Email zhuyj@smmu.edu.cnAbstract: Acrodermatitis enteropathica (AE) can be caused by inherited or acquired zinc deficiency, among which site-specific skin lesions or even psoriasiform skin manifestations are present. Few cases exist in the literature involving the diagnosis and treatment of AE overlapped with psoriasiform lesions. In this case, we reported a teenage boy presented characteristic site-specific skin lesions of AE with low serum zinc level, subsequently progressed into generalized pustular psoriasiform manifestations under a genetic background, while a rapid recovery was observed after monotherapy of zinc supplementation. Since zinc malabsorption was suspend to be the trigger of both AE and psoriasiform lesions, simply maintaining balanced zinc homeostasis might be a safe and effective treatment for the overlapped manifestations.Keywords: acrodermatitis enteropathica, psoriasis, zinc